Uji Resistensi dan Sensitivitas Bakteri Salmonella thypi Pada Orang Yang Sudah Pernah Menderita Demam Tifoid Terhadap Antibiotik - Nur Indang; Musjaya M. Guli; Muhammad Alwi (Biocelebes, 2013)
This Research explores “The Resistance and Sensitivity Test of Salmonella thypi Bacteria of the People Who Had Ever Suffered from the Typhoid Fever toward the Antibiotic”, in which it was conducted on January to March 2013 at UPT Health Laboratory Palu Central Sulawesi. The objective of the research was to recognize the kind of antibiotics that is resistant and sensitive, and was to know the capacity zone of inhibition that was generated by the administering of antibiotic toward Salmonella thypi bacteria against people who had ever suffered from the typhoid fever. The researcher employed biochemical test, resistance and sensitivity test of Salmonella thypi bacteria toward the antibiotic. The findings shows that Salmonella thypi Bacteria is resistant toward the four kinds of antibiotics, they are 5.95 mm of Ampicillin, 6.9 mm of Amoxicillin, 7.9 mm of Cephalexin, and 8.1 mm of Chloramphenicol, and the Salmonella thypi Bacteria is sensitive toward four kinds of antibiotics, they are 21.35 mm of Cefatoxime, 22.6 mm of ceftazidime, 23.4 mm of Cefaperazone and 25.95 mm of Ceftriaxone. The most effective antibiotic to block the growth of Salmonella thypi bacteria is a Sefalosporin group of the third generation, they are Ceftriaxone, Cefoperazone, Ceftazidime, dan Cefatoxime. Key words: Typhoid Fever, Resistance and Sensitivity Test, Antibiotics, Salmonella thypi.